Shipboard ADCP current measurements (75 kHz) during RV SONNE cruise SO300/1 - Kopte, Robert; Barckhausen, Udo; Bissessur, Prithivi Dass (PANGAEA, 2024)
Current velocities of the upper water column along the cruise track of R/V Sonne cruise SO300/1 were collected by a vessel-mounted 75 kHz RDI Ocean Surveyor ADCP. The ADCP transducer was located at 6.0 m below the water line. The instrument was operated in narrowband mode (WM10) with a bin size of 8.00 m, a blanking distance of 8.00 m, and a total of 100 bins, covering the depth range between 22.0 m and 814.0 m. Heading, pitch and roll data from the ship's motion reference unit and the navigation data from the Global Positioning systems were used by the data acquisition software VmDAS internally to convert ADCP velocities into earth coordinates. The ship's velocity was calculated from position fixes obtained by the Global Positioning System (GPS). Accuracy of the ADCP velocities mainly depends on the quality of the position fixes and the ship's heading data. Further errors stem from a misalignment of the transducer with the ship's centerline. Data post-processing included water track calibration of the misalignment angle (-0.1371° +/- 0.5235°) and scale factor (0.9973 +/- 0.0078) of the Ocean Surveyor signal. The velocity data were averaged in time using an average interval of 120 s. Velocity quality flagging is based on different threshold criteria: Depth cells with ensemble-averaged percent-good values below 25% are marked as 'bad data'. Depth cells with velocities above 1.5 m/s are flagged as 'bad data'. Depth cells with a root-mean-square deviation between the measured ensemble-average velocity and a cell-wise running-mean velocity above 0.3 m/s are flagged as 'probably bad data'.